Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð±Ð°Ñ€Ð±Ð¸Ñ‚ÑƒÑ€Ð°Ñ‚Ð¾Ð² Ð¸ Ð»Ð¸Ð´Ð¾ÐºÐ°Ð¸Ð½Ð° Ð½Ð° ÑƒÑÑ‚Ð¾Ð¹Ñ‡Ð¸Ð²Ð¾ÑÑ‚ÑŒ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ðº Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¾Ð¼Ñƒ Ð³ÐµÐ¼Ð¾Ð»Ð¸Ð·Ñƒ - Prokopenko, N. V.; Bondarenko, V. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Dynamics of erythrocyte hemolysis under transferring them into hypertonic solution (4.0 mol/l NaCl) with introduced barbital, phenobarbital and lidocaine at 37 and 0Â°C has been studied. Barbiturates and lidocaine were established to increase cell integrity under hypertony at 37 and 0Â°C. Protective effect is more manifested in phenobarbital. Under preliminary cell dehydration the erythrocyte integrity augments after dehydration in moderately hypertonic media. In that case barbiturates and lidocaine increase cell integrity as well.